2015
DOI: 10.2320/matertrans.m2014391
|View full text |Cite
|
Sign up to set email alerts
|

Photoassisted Electrodeposition of a Copper(I) Oxide Film

Abstract: Photoassisted electrodeposition of a cuprous oxide (Cu 2 O) thin film was studied to find the optimum conditions lowering the deposition temperature. Cu 2 O films were electrochemically deposited on FTO by cycling the electrode potential between 0.0 V and ¹0.8 V (Ag«AgCl), in an aqueous solution. A simple deposition cell was designed to allow simultaneous thermostating and polychromic illumination. Under illumination, the Cu 2 O film deposition occurred, even at a temperature lower than the temperature observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The diffraction rings marked with red, yellow, green, and blue dashed lines correspond to the (111), (200), (220), and (311) crystal faces of Cu 2 O, respectively. The result was consistent with its XRD pattern (Figure b) according to the Joint Committee on Powder Diffraction Standards (JCPDS) PDF#05-0667 . Furthermore, high-resolution transmission electron microscopy (HRTEM) image of a single Cu 2 O QW is illustrated in Figure c.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The diffraction rings marked with red, yellow, green, and blue dashed lines correspond to the (111), (200), (220), and (311) crystal faces of Cu 2 O, respectively. The result was consistent with its XRD pattern (Figure b) according to the Joint Committee on Powder Diffraction Standards (JCPDS) PDF#05-0667 . Furthermore, high-resolution transmission electron microscopy (HRTEM) image of a single Cu 2 O QW is illustrated in Figure c.…”
Section: Resultssupporting
confidence: 81%
“…The result was consistent with its XRD pattern (Figure 3b) according to the Joint Committee on Powder Diffraction Standards (JCPDS) PDF#05-0667. 54 the unavoidable byproduct in the synthesis. Further, Figure S3b shows the Cu + LMM Auger peak located at 570 eV, which confirmed that the as-prepared QWs consisted of Cu 2 O.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Many studies reported several approaches to synthesize CZTS thin films including chemical and physical processes [12][13][14]. Due to many advantages of the chemical processes (non-vacuum) over the physical processes (vacuum)such as simplicity, scalability, cost effectiveness, low-temperature deposition capacity, and manufacturability, electrodeposition has been widely used to prepare photovoltaic CZTS thin films [15][16][17][18][19][20]. The used electrodeposition techniques include (i) sequential electrodeposition of metallic stacked thin layers on copper (Cu), zinc (Zn), and tin (Sn) followed by sulfur (S) diffusion, (ii) simultaneous electrodeposition of metallic Cu, Zn, and Sn thin film followed by S diffusion and (iii) single step electrodeposition of CZTS thin film followed by S diffusion [21][22][23].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…PVP acts as a capping surfactant reagent, which is adsorbed differently on various crystal surfaces and leads to a competitive growth between different copper crystal facets, and results in shape variation of the final crystal shape. According to the literature [31,[34][35][36][37], some of possible reactions in an aqueous solution of copper during the electrodeposition are as follows:…”
Section: Introductionmentioning
confidence: 99%